Educational and Methodical Support of Creative Works in the Process of Professional and Pedagogical Training - Savka, Iryna; Yakymovych, Tetiana (Pedagogical Discourse, 2021)
The purpose of the study is to test the effectiveness of scientific and methodological support of creative work in the process of professional and pedagogical training. In the course of the research it is found that the increase in the efficiency level of professional and professional training of the future vocational school teachers can take place on the basis of extensification and intensification. The necessity of creative works in the process of professional and pedagogical training is substantiated. It is determined that creative work can be considered as a process and result of activity; the result of professional and pedagogical training; implementation of creative ideas in professional activities. There are revealed the peculiarities of training and evaluation of creative works of future teachers of vocational training. There is studied the effectiveness of the factors of subjective influence on the performance of creative work, as well as the influence of the components of educational and methodological support on the process of performing creative work and the effectiveness of the criteria for evaluating creative work. There is proved the effectiveness of educational and methodological support at the stages of preparation, implementation, evaluation of creative work in the process of professional and pedagogical training of future vocational schools teachers.